Foci and Bases of Commitment: Are They Distinctions Worth Making? - Becker, Thomas E. (Academy of Management Journal, 1992)
This study examined the contribution of two concepts to the conventional view of commitment: foci of commitment, the individuals and groups to whom an employee is attached, and bases of commitment, the motives engendering attachment. Commitment to top management, supervisor, and work group were important determinants of job satisfaction, intent-to quit, and prosocial organizational behaviors over and above commitment to an organization. Compliance, identification, and internalization as bases of commitment were unique determinants above and beyond commitment to the foci.